Corporate turnaround strategies and management accounting reorientation of Malaysian companies / Hanafiah Hasin - Hasin, Hanafiah (Institute of Graduate Studies, UiTM, 2014)
Market erosion and maladaptive management decisions have been the causes for declining financial performance of firms at some point of the organizational life cycle, which resulted to a situation of organizational decline. In this context, this research was undertaken to examine the causes of corporate decline and the strategies that could be employed to turnaround the organizations. Exploring the role and utility of management accounting practices as effective organizational strategies to face the challenges of decline is the central focus of the study. A research design of a review of the relevant literature, followed by a quantitative survey among Malaysian companies, which have experienced organizational decline and the case study of the management accounting practices of Lighting Company in Malaysia was adopted to achieve the objectives of the study. Based on the review of the literature the study concludes that internal organizational factors as compared external environmental factors are more responsible for causing organizational decline.